2014
DOI: 10.1179/2045772314y.0000000239
|View full text |Cite
|
Sign up to set email alerts
|

Testing the feasibility of training peers with a spinal cord injury to learn and implement brief action planning to promote physical activity to people with spinal cord injury

Abstract: Objective: The present study tested the feasibility of training peers with spinal cord injury (SCI) to learn brief action planning (BAP), an application of motivational interviewing principles, to promote physical activity to mentees with SCI. Method: Thirteen peers with SCI attended a half-day BAP workshop. Using a one-arm, pre-, post-test design, feasibility to learn BAP was assessed in terms of peers' (1) BAP and motivational interviewing spirit competence; (2) training satisfaction; and (3) motivations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…In this study, it was suggested that peers, along with therapists, may be a valuable combination for delivering fall prevention training. Peer mentoring has been employed in interventions for individuals with SCI40 41 but has not yet been explored as a potentially viable fall prevention training method. Future research should investigate the utility of peer mentoring in fall prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was suggested that peers, along with therapists, may be a valuable combination for delivering fall prevention training. Peer mentoring has been employed in interventions for individuals with SCI40 41 but has not yet been explored as a potentially viable fall prevention training method. Future research should investigate the utility of peer mentoring in fall prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results suggest that brief motivational work can help to support self-management and motivate adaptive health behavior change following SCI. 34 Another consideration for future Work and SCI trials is the screening process. Given that up to 60% of people with traumatic SCI have concurrent TBI, which often has not been diagnosed, 35,36 and whilst a third have lowered cognitive capacity due to SCI complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate whether group-based and peer-led approaches to deliver fall prevention education would be feasible and effective in this population. Peer-based approaches to learning skills for people with spinal cord injury have previously been successful [64,65], but have not been used for fall prevention [13].…”
Section: Plos Onementioning
confidence: 99%